Ethical Financial Management Practices and Organizational Resilience: The Mediating Role of Financial Transparency and Cooperative Culture in Credit Unions - Sarlawa, Rita; Widyaningsih, Dhina Sri (Jurnal Locus Penelitian dan Pengabdian, 2026)
Credit unions continue to face challenges arising from economic crises and rapid digital transformation, making organizational resilience (OR) increasingly essential. This study investigates whether Ethical Financial Management Practices (EFMP) contribute to strengthening OR both directly and indirectly through Financial Transparency and Responsibility (FTR) and Cooperative Culture (CC). Using survey data from 381 administrators and members of credit unions, analyzed with GSCA Smart PLS, the study found that all proposed relationships were statistically significant. EFMP demonstrated a positive influence on FTR, while both FTR and CC significantly affected OR. Furthermore, FTR and CC were shown to partially mediate the relationship between EFMP and OR. These findings highlight that ethical practices, transparency, and cooperative cultural values operate as mutually reinforcing mechanisms that enhance resilience by fostering trust, minimizing information asymmetry, improving accountability, and encouraging member participation. Integrating EFMP with strong transparency mechanisms and cooperative values provides a comprehensive governance framework that supports sustainable and resilient credit union operations. Practically, the study suggests that leadership should institutionalize ethical financial standards, improve disclosure quality, strengthen accountability practices, and create inclusive participatory routines to sustain member trust and organizational adaptability in the face of uncertainty and systemic disruptions.